Analisis Bibliometrik Penelitian tentang Art Counseling Berdasarkan Data Scopus Tahun 2020–2025 - Vira Afriyati; Widya Kartika Sari; Arsyadani Misbahudin (Empowerment Counseling Journal, 2025)
This study aims to analyze the development of research on art counseling in the 2020–2025 period based on data from the Scopus database. This study uses a bibliometric approach to map publication trends, source journals, country and institutional collaborations, and scientific fields that contribute to the development of art counseling. The analysis results show that there are 158 scientific articles that meet the criteria, with the document type being all journal articles. Publications on art counseling show a steady upward trend throughout the study period. The most productive journal is the Journal of Creativity in Mental Health, followed by AIDS and Behavior and AIDS Care: Psychological and Socio-Medical Aspects of AIDS/HIV. The country with the highest number of publications is the United States, followed by South Africa, the United Kingdom, China, and Canada. The majority of research is in psychology (46.9%), followed by medicine (31.8%) and social sciences (16.3%), with dominant funding support coming from United States health agencies such as the NIH and USAID. These findings indicate that art counseling is developing as a powerful interdisciplinary approach, especially in the context of mental health, psychosocial interventions, and trauma recovery, and open up opportunities for broader research development in the field of counseling and counselor education in the future.